Effects of intellectual property rights protection on services export diversification in developing countries - Sèna Kimm Gnangnon (KDI Journal of Economic Policy, 2024)
The effects of the betterment of enforced intellectual property rights (IPRs) provisions on services export diversification are investigated. The analysis used an unbalanced panel dataset of 76 developing countries over the period of 1970-2014. The empirical analysis is based on the feasible generalized least squares estimator. It suggests that the implementation of weaker IPR protection fosters services export diversification in less developed countries (i.e., those whose real per capita incomes are less than US 1458.60), including those with a low level of export product upgrading. Conversely, in relatively advanced developing countries (countries whose real per capita income exceeds US 3356.80), including those with high levels of export product upgrading, the implementation of stronger IPR laws induces greater services export diversification. Finally, the analysis revealed the existence of a non-linear relationship between IPR protection and services export diversification. The implementation of stronger intellectual property laws spurs services export diversification in countries with high degree of IPR protection, especially when IPR protection exceeds a certain level, recorded here as having a score of 1.197. In contrast, in countries with weaker IPR protection, in particular those with IPR protection levels that score less than 0.915, it is rather the implementation of weaker intellectual property laws that promotes services export diversification.
Keywords: E31; F13; O34; 330; Intellectual Property Rights; Services Export Diversification; Export Product Upgrading; Developing Countries